Maize and pigeon pea production, profitability, and tied credit in Southern Shan state - Belton, Ben; Fang, Peixun (Michigan State University, 2020)
This report presents results from by far the most comprehensive survey of maize cultivators ever conducted in Myanmar. This research was designed to test characterizations of hybrid maize farming in the literature on Myanmar empirically, and identify implications for development policy and programming. A study by the World Bank (2016) suggests that returns from maize farming are very high in comparison to other major crops grown in Myanmar, whereas two studies by Woods (2015a; 2015b) list a host of negative impacts associated with hybrid maize cultivation, including reduced food security, widespread and severe indebtedness among the smallest farmers, and deepening inequality. Our survey represented the population of all maize growing village tracts in the nine major maize growing townships of southern Shan where the security situation at the time of the survey permitted access. A total 884 maize growing and 678 non-maize growing rural households were interviewed. We summarize key survey results and their implications below.